Utility of Amyloid and FDG-PET in Clinical Practice: Differences Between Secondary and Tertiary Care Memory Units. - Lage, Carmen; Suarez, Andrea Gonzalez; Pozueta, Ana; Riancho, Javier; Kazimierczak, Martha; Bravo, María; Jimenez Bonilla, Julio; de Arcocha Torres, Marıa; Quirce, Remedios; Banzo, Ignacio; Vázquez-Higuera, José Luis; Rabinovici, Gil D; et al. (J Alzheimers Dis, 2018)
The clinical utility of amyloid positron emission tomography (PET) has not been fully established. Our aim was to evaluate the effect of amyloid imaging on clinical decision making in a secondary care unit and compare our results with a previous study in a tertiary center following the same methods. We reviewed retrospectively 151 cognitively impaired patients who underwent amyloid (Pittsburgh compound B [PiB]) PET and were evaluated clinically before and after the scan in a secondary care unit. One hundred and fifty concurrently underwent fluorodeoxyglucose (FDG)-PET. We assessed changes between the pre- and post-PET clinical diagnosis and Alzheimer's disease treatment plan. The association between PiB/FDG results and changes in management was evaluated using χ2 and multivariate logistic regression. Concordance between classification based on scan readings and baseline diagnosis was 66% for PiB and 47% for FDG. The primary diagnosis changed after PET in 17.2% of cases. When examined independently, discordant PiB and discordant FDG were both associated with diagnostic change (p < 0.0001). However, when examined together in a multivariate logistic regression, only discordant PiB remained significant (p = 0.0002). Changes in treatment were associated with concordant PiB (p = 0.009) while FDG had no effect on treatment decisions. Based on our regression model, patients with diagnostic dilemmas, a suspected non-amyloid syndrome, and Clinical Dementia Rating <1 were more likely to benefit from amyloid PET due to a higher likelihood of diagnostic change. We found that changes in diagnosis after PET in our secondary center almost doubled those of our previous analysis of a tertiary unit (9% versus 17.2%). Our results offer some clues about the rational use of amyloid PET in a secondary care memory unit stressing its utility in mild cognitive impairment patients.

MicroRNA Profile in Patients with Alzheimer's Disease: Analysis of miR-9-5p and miR-598 in Raw and Exosome Enriched Cerebrospinal Fluid Samples. - Riancho, Javier; Vázquez-Higuera, José Luis; Pozueta, Ana; Lage, Carmen; Kazimierczak, Martha; Bravo, María; Calero, Miguel; Gonalezález, Andrea; Rodríguez, Eloy; Lleo, Alberto; Sánchez-Juan, Pascual (J Alzheimers Dis, 2017)
BACKGROUND: MicroRNAs have been postulated as potential biomarkers for Alzheimer's disease (AD). Exosomes are nanovesicles which transport microRNAs, proteins, and other cargos. It has been hypothesized that the exosome traffic might be increased in neurodegenerative disorders. OBJECTIVE: i) To assess the cerebrospinal fluid (CSF) microRNA profile in a group of AD patients and control subjects and to validate a group of microRNAs previously reported by other authors. ii) To compare microRNA levels in whole CSF and in the exosome-enriched fraction in AD patients. METHODS: A panel of 760 microRNAs was analyzed in the CSF of 10 AD patients and 10 healthy subjects. Among microRNAs differently expressed, we selected those that had been previously reported by other authors. Candidates were validated in a larger group by individual qPCR assays. MicroRNA expression was also evaluated in exosome-enriched CSF samples of patients with AD and controls. RESULTS: Fifteen microRNAs were differently expressed in AD. MiR-9-5p, miR-134, and miR-598 were selected as candidates for further analysis. MiR-9-5p and miR-598 were detected in 50 and 75% of control CSF samples, respectively, while they were not detected in any AD CSF samples. We observed an opposite pattern when we evaluated the microRNA expression in the exosome-enriched CSF AD samples. No pattern variations were noted among healthy subjects. CONCLUSION: These data propose miR-9-5p and miR-598 as potential biomarkers for AD. Further studies in plasma and other body fluids will confirm their potential role as easily accessible biomarkers. In addition, our data suggest that exosome trafficking is different between AD and control subjects raising the need to take this phenomenon into consideration in future studies of AD biomarkers.